(untitled) (European Journal of Marketing and Economics, 2022)
Interim management is a situation that virtually every leader will encounter at least once in their career. On an organizational level, unplanned vacancies may occur for a variety of reasons including personnel rotations, illness, organizational re-structuring, or performance. While the situation is common, most organizations approach interim leadership on an ad-hoc basis and do not have the structures or support systems in place to effectively manage interim leadership needs. This article distills and integrates interim leadership research into an assessment approach and application across managerial levels and organizational types. This approach serves as an avenue for the Human Resource practitioner to understand, develop, and adapt organizational policy and support systems to prepare for interim management needs.